Multiplexing Error and Noise Reduction in Electrical Impedance Tomography Imaging - Barreiro, Martina; Sánchez, Pablo; Vera, Julián; Viera, Matías; Morales, Isabel; Dell´Osa, Antonio Hector; Bertemes-Filho, Pedro; Simini, Franco (Frontiers in Electronics, 2022)
Electrical Impedance Tomography design can be simplified to obtain a low cost 16 electrodes edema monitoring clinical instrument by using voltage measurement multiplexing. Multiplexers add considerable noise, which we have estimated by consecutive phantom measurements both using voltage multiplexers and by selecting the electrodes by hand, all other things being the same. The EIDORS reconstruction of the phantom with an object inside by hand-selected electrodes measurements and the multiplexed measurements are compared to the reconstruction of the conductivity of the phantom with no objects. The estimation of the difference (i.e. the error) at each electrode is obtained by averaging across all measurements for each electrode, irrespective of the injection electrode pair. This measurement error is subtracted from the multiplexed measurement matrix, giving a modified reconstruction which is closer to the hand-selected electrodes measurement based reconstruction than the multiplexed reconstruction. The quality factor of the uncorrected multiplexer-obtained image of 57% is increased to 83% which is the best increase of three methods described. This could suggest the benefit of a calibration phase for all 16 electrodes, prior to EIT reconstruction, using a set-up-specific “error matrix” to correct the data matrix before submission to the reconstruction method.